Sustainable Business Transformation: Digital Leadership and Skill Development Through Motivational Catalysts for Superior Performance - Hadiwijaya, Eka (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to determine the influence of digital leadership and skill development on motivation and performance at the DRAB hospital. This study uses a quantitative approach with Structural Equation Modeling (SEM) analysis. This study used a questionnaire with proportional random sampling techniques on 360 people from 718 total employees, with Likert scale measurements. The results of the study show that Digital Leadership, skill development has a significant positive effect on motivation, Digital Leadership, skill development and motivation have a significant positive effect on Superior Performance, Digital Leadership has a significant positive effect on Superior Performance through motivation, skill Development has a significant positive effect on Superior Performance through motivation.